Nutritional strategies of British professional and amateur natural bodybuilders during competition preparation. Issue 1 (22nd August 2019) - Chappell, A. J.; Simper, T.; Helms, E.
Abstract: Background: To prepare for competition, bodybuilders employ strategies based around: energy restriction, resistance training, cardiovascular exercise, isometric "posing", and supplementation. Cohorts of professional (PRO) natural bodybuilders offer insights into how these strategies are implemented by elite competitors, and are undocumented in the scientific literature. Methods: Forty-seven competitors (33 male (8 PRO, 25 amateur (AMA), 14 female (5 PRO, 9 AMA) participated in the study. All PROs were eligible to compete with the Drug Free Athletes Coalition (DFAC), and all AMAs were recruited from the British Natural Bodybuilding Federation (BNBF). Competitors in these organisations are subject to a polygraph and are drug tested in accordance with the World Anti-Doping Agency. We report the results of a cross-sectional study of drug free bodybuilders competing at BNBF qualifying events, and the DFAC and World Natural Bodybuilding Federation finals. Participants completed a 34-item questionnaire assessing dietary intake at three time points (start, middle and end) of competition preparation. Participants recorded their food intake over a 24-h period in grams and/or portions. Dietary intakes of PRO and AMA competitors were then compared. Repeated measures ANOVA was used to test if nutrient intake changed over time, and for associations with division. Results: Male PROs reported significantly ( p < 0.05) more bodybuilding experience than AMAs (PRO: 12.3 +/− 9.2, AMA: 2.4 +/− 1.4 yrs). Male PROs lost less body mass per week (PRO: 0.5 +/− 0.1, AMA: 0.7 +/− 0.2%, p < 0.05), and reported more weeks dieting (PRO: 28.1 +/− 8.1, AMA: 21.0 +/− 9.4 wks, P = 0.06). Significant differences ( p < 0.05) of carbohydrate and energy were also recorded, as well as a difference ( p = 0.03) in the estimated energy deficit (EED), between male PRO (2.0 +/− 5.5 kcal) and AMA (− 3.4 +/− 5.5 kcal) competitors. Conclusions: Longer diets and slower weight loss utilized by PROs likely contributed towards a lower EED compared to the AMAs. Slower weight loss may constitute an effective strategy for maintaining energy availability and muscle mass during an energy deficit. These findings require corroboration, but will interest bodybuilders and coaches.